Identifikasi Pendekat Dominan dan Analisis Sensitivitas Kapasitas Simpang APILL Patung Kirab Kota Kupang Berdasarkan PKJI 2023 - Benny Tua Siahaan; Adveni Hesty Altisari Lada; Ari Esclesias Sinaga; Alvin Alfredo Bara (Jurnal Kridatama Sains dan Teknologi, 2026)
Urban traffic growth increases operational pressure on signalized intersections, particularly in areas serving commercial, office, educational, and residential activities. This study evaluates capacity, operational performance, and critical approaches at the Patung Kirab signalized intersection in Kupang City based on the Indonesian Road Capacity Guidelines 2023 (PKJI 2023). The novelty of this study lies in integrating aggregate intersection performance evaluation with approach-based flow distribution analysis and capacity-improvement sensitivity scenarios to determine operational treatment priorities for a medium-sized city in Eastern Indonesia. A descriptive quantitative approach was applied through classified traffic-volume surveys, geometric observations, signal-timing observations, and side-friction observations over three days: Sunday 9 November 2025, Monday 10 November 2025, and Tuesday 11 November 2025. Surveys were conducted during three periods, namely 06:00–08:00, 12:00–14:00, and 18:00–20:00 WIT, and the analysis hour was selected based on the highest traffic volume for each observation day. The results show that the intersection capacities on Sunday, Monday, and Tuesday were 3,734.08, 3,645.51, and 3,589.57 skr/hour, respectively. The corresponding degrees of saturation were 0.739, 1.139, and 0.936, while the average delays were 4.125, 29.220, and 16.604 seconds/skr. Monday was oversaturated, whereas Tuesday operated in a critical range. The southern approach was dominant on Sunday and Monday, contributing 40.71% and 40.66% of total traffic flow, whereas the western approach was dominant on Tuesday, contributing 41.75%. The sensitivity analysis indicates that a 10% capacity increase would only reduce Monday's degree of saturation to 1.035, while Tuesday would decrease close to the planning threshold at 0.851. These findings indicate that initial treatments should prioritize green-time optimization for the southern and western approaches, side-friction control, and queue observation during peak hours